Consumer Behavior towards Safer Car Purchasing Decisions - Khairil Anwar Abu Kassim; Mohd Hafzi Md Isa; Yahaya Ahmad; Intan Osman; Lawrence Arokiasamy (Journal of Engineering and Technological Sciences, 2016)
In Malaysia, the car safety level has been elevated through regulations and a consumer-based approach, i.e. the New Car Assessment Program in Southeast Asian Countries (ASEAN NCAP). Nevertheless, the availability of information on consumers' car purchasing decisions towards safety is still limited in Malaysia. Thus, this study was aimed at evaluating consumers' purchasing decisions of their present cars and investigating their awareness of ASEAN NCAP. Self-administered questionnaires were distributed among consumers visiting different car showrooms and dealer shops. The findings suggest that safety was considered as one of the top three factors by the respondents when purchasing their present cars. Awareness of ASEAN NCAP has increased as compared to a previous study. This information is essential for policy makers, manufacturers and other stakeholders to assist in setting priorities with regard to the promotion of car safety in the country.